Substance use, risk behaviours and well-being after admission to a quasi-residential abstinence-based rehabilitation programme: 4-year follow-up. Issue 2 (13th March 2023) - MacKenzie, Nina; Smith, Daniel J.; Lawrie, Stephen M.; M. Rome, Andrew; McCartney, David
Abstract : Background: Tackling Scotland's drug-related deaths and improving outcomes from substance misuse treatments, including residential rehabilitation, is a national priority. Aims: To analyse and report outcomes up to 4 years after attendance at a substance misuse residential rehabilitation programme (Lothians and Edinburgh Abstinence Programme). Method: In total, 145 participants were recruited to this longitudinal quantitative cohort study of an abstinence-based residential rehabilitation programme based on the therapeutic community model; 87 of these participants were followed up at 4 years. Outcomes are reported for seven subsections of the Addiction Severity Index-X (ASI-X), together with frequency of alcohol use, heroin use, injecting drug use and rates of abstinence from substances of misuse. Results: Significant improvement in most outcomes at 4 years compared with admission scores were found. Completing the programme was associated with greater rates of abstinence, reduced alcohol use and improvements in alcohol status score (Mann–Whitney U = 626, P = 0.013), work satisfaction score ( U = 596, P = 0.016) and psychiatric status score ( U = 562, P = 0.007) on the ASI-X, in comparison with non-completion. Abstinence rates improved from 12% at baseline to 48% at 4 years, with the rate for those completing the programme increasing from 14.5% to 60.7% (χ 2 (2, 87) = 9.738, P = 0.002). Remaining abstinent from substances at follow-up was associated with better outcomes in the medical ( U = 540, P < 0.001), psychiatric ( U = 273.5, P < 0.001) and alcohol ( U = 322.5, P < 0.001) subsections of the ASI-X. Conclusions: Attending this abstinence-based rehabilitation programme was associated with positive changes in psychological and social well-being and harm reduction from substance use at 4-year follow-up, with stability of change from years 1 to 4.